Myc inhibition impairs autophagosome formation - Toh, Pearl P. C. (Oxford University Press, 2013)
Autophagy, a major clearance route for many long-lived proteins and organelles, has long been implicated in cancer development. Myc is a proto-oncogene often found to be deregulated in many cancers, and thus is an attractive target for design of cancer therapy. Therefore, understanding the relationship between anti-Myc strategies and autophagy will be important for development of effective therapy. Here, we show that Myc depletion inhibits autophagosome formation and impairs clearance of autophagy substrates. Myc suppression has an inhibitory effect on autophagy via reduction of c-Jun N-terminal kinase 1 (JNK1) and B-cell lymphoma 2 (Bcl2) phosphorylation. Additionally, the decrease in JNK1 phosphorylation observed with Myc knockdown is associated with a reduction in ROS production. Our data suggest that targeting Myc in cancer therapy might have the additional benefit of inhibiting autophagy in the case of therapy resistance associated with chemotherapy-induced autophagy.